Pengaruh Persepsi PKL Dan Motivasi Memasuki Dunia Kerja Terhadap Kesiapan Kerja Siswa Kelas XI - Nadya Falensia Lovie; Patni Ninghardjanti; Tri Murwaningsih (Politeknik Kampar, 2023)
This study aims to (1) determine the effect of perceptions of field work practices on the work readiness of class XI students of SMK Wikarya Karanganyar; (2) determine the influence of motivation to enter the world of work on the work readiness of class XI students at SMK Wikarya Karanganyar; (3) determine the effect of perceptions of field work practices and motivation to enter the world of work together on the work readiness of class XI students at SMK Wikarya Karanganyar. The research design used is descriptive research with a quantitative approach. The results of the study are as follows: (1) there is a positive and significant effect of perceptions of field work practices on students' work readiness. This is indicated by the value of tcount>ttable (4.609>1.985) and for a significance value of 0.000 (Sig<0.05); (2) there is a positive and significant influence of motivation to enter the world of work on students' work readiness. This is indicated by the value of tcount>ttable (3.537>1.985) and for a significance value of 0.001 (Sig<0.05); and (3) there is a positive and significant influence simultaneously on the perception of employment practices and motivation to enter the world of work on student work readiness. This is indicated by the value of Fcount>Ftable (65.881>3.091) and for a significance value of 0.000 (Sig<0.05). This study aims to (1) determine the effect of perceptions of field work practices on the work readiness of class XI students of SMK Wikarya Karanganyar; (2) determine the influence of motivation to enter the world of work on the work readiness of class XI students at SMK Wikarya Karanganyar; (3) determine the effect of perceptions of field work practices and motivation to enter the world of work together on the work readiness of class XI students at SMK Wikarya Karanganyar. The research design used is descriptive research with a quantitative approach. The population in this study were 131 students of class XI at SMK Wikarya Karanganyar. The research sample consisted of 99 students who were taken using the proportional random sampling technique. The data collection technique used was a questionnaire used to measure the effect of perceptions of field work practices and motivation to enter the world of work on work readiness. The data analysis technique used is descriptive statistical analysis and multiple linear regression analysis. The results of the study are as follows: (1) there is a positive and significant effect of perceptions of field work practices on students' work readiness. This is indicated by the value of tcount>ttable (4.609>1.985) and for a significance value of 0.000 (Sig<0.05); (2) there is a positive and significant influence of motivation to enter the world of work on students' work readiness. This is indicated by the value of tcount>ttable (3.537>1.985) and for a significance value of 0.001 (Sig<0.05); and (3) there is a positive and significant influence simultaneously on the perception of employment practices and motivation to enter the world of work on student work readiness. This is indicated by the value of Fcount>Ftable (65.881>3.091) and for a significance value of 0.000 (Sig<0.05).